Center-of-Gravity Variation-Driven Spherical UAV System and Its Control Law - Donghoon Kim; Sungwook Yang (International Journal of Aerospace Engineering)
Most of the spherical unmanned aerial vehicles (SUAVs) use control surfaces, which are functions of aileron and an elevator, to generate control torque. The work proposes a new conceptual design of an SUAV system controlled through center-of-gravity (CG) variations with its path-tracking control law designed for the system. Compared to the one using control surfaces, the concept suggested is beneficial in the aspect of the expandability of building lighter and smaller SUAVs, especially. A CG variation principle by actuating a pendulum type of a moving part is considered as a methodology for both translational and rotational motion control of an SUAV. Since variations of the moment-of-inertia (MOI) elements which resulted from the motion of the moving part affect the performance of the suggested method, the variations of MOI analysis are performed for all angular ranges of the moving part. As a result, certain angular ranges for the moving part to prevent the degradation of the path-tracking performance by the effect of the MOI changes are found. By considering the findings, numerical studies are performed for hovering, ascent, descent, and horizontal tracking missions. The applicability of the proposed SUAV system and the corresponding controller to achieve the path-tracking missions is demonstrated through the numerical simulation.